Human interaction: Dissipative structure and will to power - Montoya Carvajal, Juan Fernando; Garcés Giraldo, Luis Fernando; Giraldo, Conrado de Jesús (Revista de Ciencias Sociales, 2025)
The main theme of this work is the relationship between entropy and the concept of the will to power, aiming to offer a perspective on the transformation of reality based on the relationship between science and philosophy. This project emerges from the concept of entropy (the second law of thermodynamics) as a quantity that determines the irreversibility of a process and the concept that explains the cause of natural transformation, tending toward a permanent increase in the universe, which underlies the degradation of systems and the convergence toward chaos. As a hermeneutic instrument for interpreting social interaction, this work uses thermodynamics as an argumentative tool framed within a philosophical and epistemological context, seeking to describe the logical